Foods of Iceland - Sheen, Barbara (Farmington Hills, Michigan : Lorenz Books, 2011)
Discusses the role of food in Icelandic culture and common ingredients found in the country's cuisine, and includes recipes for traditional desserts, main courses, and appetizers.
Pure healthy food -- Simple and hearty -- Afternoon treats -- Celebrating with traditional foods.
Includes index.
Keywords: COOKING, ICELANDIC -- JUVENILE LITERATURE